2020
DOI: 10.3389/fbioe.2020.00847
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Application of Supramolecular Hydrogels for Stem Cell Delivery and Cartilage Tissue Engineering

Abstract: Cartilage defects pose a great threat to the health of the aging population. Cartilage has limited self-regeneration ability because it lacks blood vessels, nerves and lymph. To achieve efficient cartilage regeneration, supramolecular hydrogels are used in medical applications and tissue engineering as they are tunable and reversible in nature. Moreover, they possess supramolecular interactions which allow the incorporation of cells. These hydrogels present great potential for tissue engineering-based therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…Numerous scientific reports have focused on the use of molecular hydrogels in the regeneration of cartilage and bone [ 1 , 29 , 151 ]. Hou et al prepared an injectable supramolecular hydrogel based on dextran by grafting a significant number of multiple-hydrogen-bond (ureidopyrimidinone) [ 152 ].…”
Section: Supramolecular Hydrogels As Carriers For Biologically Active Substancesmentioning
confidence: 99%
“…Numerous scientific reports have focused on the use of molecular hydrogels in the regeneration of cartilage and bone [ 1 , 29 , 151 ]. Hou et al prepared an injectable supramolecular hydrogel based on dextran by grafting a significant number of multiple-hydrogen-bond (ureidopyrimidinone) [ 152 ].…”
Section: Supramolecular Hydrogels As Carriers For Biologically Active Substancesmentioning
confidence: 99%
“…Cartilaginous tissue possesses a hydrated heterogeneous and avascular structure with specific characterizations of low friction, wear-resistant, and load-bearing surfaces for effective joint protection and movement ( Yan et al, 2020 ). Although many conventional surgical treatments have been proposed for chondral injuries, few clinical studies have shown the reliable regeneration of normal hyaline cartilage due to its poor self-healing capacity originating from the insufficient supply for defected sites.…”
Section: Polymer-based Bioprinting Hydrogels For Cartilage Tissue Engineeringmentioning
confidence: 99%
“…Hydrogels have a three-dimensional (3D) porous and interconnected structures that not only provide a biocompatible microenvironment for cell attachment and proliferation but also possess many unique advantages on the targeted drug delivery systems (Maitra and Kumar Shukla, 2014;Cao et al, 2018;Ketabat et al, 2018;Bao et al, 2019;Xu et al, 2020;Yan et al, 2020). Compared to the nanoparticlebased carriers, hydrogels provide sustained or triggered administration of both hydrophilic and hydrophobic agents and other biomolecules.…”
Section: Hydrogels For Oral Cancer Therapymentioning
confidence: 99%